(untitled) (Research, Society and Development, 2022)
Introduction: The Acquired Immunodeficiency Syndrome (AIDS) is a chronic infectious disease and one of the major global health problems. This pathology has as its causative agent the Human Immunodeficiency Virus (HIV), a retrovirus that attacks the cells of the immune system. Objective: To analyze the nursing care that can be provided to pregnant women with HIV. Method: This is a systematic review with a research method, without a time cut. The search was conducted in bibliographic databases specialized in the area of Nursing (BDENF), by consulting the Virtual Health Library (VHL); Medical Literature Analysis and Retrieval System On-line (MEDLINE), accessed through the PubMed portal. The search strategy started using terms obtained from DeCS and MESH and keywords combined with the Boolean operators (AND and OR). Result: Eight articles with evidence on nursing care for pregnant women with human immunodeficiency virus were selected. Conclusion: It is concluded that it is of utmost importance the experience of nursing professionals during prenatal care with seropositive pregnant women, providing a humanized and welcoming care in order to always promote and encourage the treatment of these pregnant women with HIV.